The Effect of Computer Simulations on Acquisition of Knowledge and Cognitive Load: A Gender Perspective. Issue 1 (2nd January 2016) - Kaheru, Sam J.; Kriek, Jeanne
Abstract : A study on the effect of the use of computer simulations (CS) on the acquisition of knowledge and cognitive load was undertaken with 104 Grade 11 learners in four schools in rural South Africa on the physics topic geometrical optics. Owing to the lack of resources a teacher-centred approach was followed in the use of computer simulations. The theoretical framework underpinning this study combines two theories, namely the cognitive load theory and the cognitive theory of multimedia learning. Within the non-equivalent group design, a switching replications design was used. In terms of the acquisition of knowledge, female learners, despite having low scores on the pre-tests, showed sizable and significant improvement in the post-tests when using CS. The measured cognitive load was not significantly different for the male and female learners. The cognitive load initially decreased as a result of teaching both through the use of CS and without use of CS in the first week while, with time, it increased.